Pengaruh yoga terhadap peningkatan kualitas tidur pada mahasiswa prodi Dııı Keperawatan Politeknik Kaltara - Sriargianti amir argi; Nining Nining; Amir Syam (Politeknik Kaltara, 2022)
Sleep is a normal activity that will be experienced by every individual and becomes a humane activity but many students do not care about the quality of good sleep so it affects their fitness level and will have a bad impact on the body. Therefore, providing yoga exercises is expected to be one way to improve sleep quality at various ages and among people with sleep quality disorders. The purpose of this study was to identify the effectiveness of yoga in improving sleep quality in university students. This research method uses a quasi-experimental design without group control which is given a pre-test and post-test. The population in the study were all students of the Politeknik Kaltara of Nursing Study Program with a total population of 131 populations. The sampling technique used purposive sampling on level 1 nursing students with a total sample of 33 samples. The research phase consists of 3 stages. The data analysis used is univariate and bivariate analysis. The results of the analysis test used McNemar and obtained ρ-value = 0.000 (<0.05) which means that there is a significant difference in the quality of sleep before and after the yoga exercise intervention. The conclusion from this study is that yoga exercises can improve sleep quality in nursing students at the Politeknik Kaltara.